2021
DOI: 10.3397/in-2021-2306
|View full text |Cite
|
Sign up to set email alerts
|

Active noise control for open windows

Abstract: Over the last decades, the applications of the active noise control system are broadened. In this study, the active noise control is modeled to reduce the noise pass through an open window. The objective is to define a suitable location for the control sources and error microphones to achieve more noise level reduction at the other side of the window. The performances of the active noise control system are calculated for two different arrangements: (1) the control sources on the edge of the opening and (2) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research has shown that active noise control significantly enhances the performance of acoustic barriers at low-frequency noise bands. [1][2][3][4] Despite the existence of various parameters that affect the efficiency of active noise barriers, few studies have optimized them. [5][6][7] Some of these parameters include the number, location, and distance between adjacent control sources and error microphones.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that active noise control significantly enhances the performance of acoustic barriers at low-frequency noise bands. [1][2][3][4] Despite the existence of various parameters that affect the efficiency of active noise barriers, few studies have optimized them. [5][6][7] Some of these parameters include the number, location, and distance between adjacent control sources and error microphones.…”
Section: Introductionmentioning
confidence: 99%